Contemporary strategy analysis : text and cases. - Grant, Robert M., 1948- (John Wiley Inc, 2014)
Robert M. Grant combines a highly accessible writing style with a concentration on the fundamentals of value creation and an emphasis on practicality in this leading strategy text. In this new edition, he includes an even greater focus on strategy implementation that reflects the needs of firms to reconcile scale economies with entrepreneurial flexibility, innovation with cost efficiency, and globalization with local responsiveness.  This edition also incorporates some of the key strategic issues of today including: post-financial crisis adjustment, the continuing rise of China, India and Brazil, and the increased emphasis on ethics and sustainability.  Coverage is also provided on strategy in not-for-profit organizations. Contemporary Strategy Analysis, Text and Cases 8th Edition combines the text with an updated collection of 20 case studies.  It is suitable for both MBA and advanced undergraduate students.